Effect of electrolyzed water and carbon dioxide microbubbles on removal of diazinon and diazoxon. (6th January 2022) - Kobayashi, Fumiyuki; Aoki, Hitoshi; Kamagata, Junichi; Odake, Sachiko
Abstract: Effect of electrolyzed water (EW) produced from sodium chloride solution in a single vessel and carbon dioxide microbubbles (CO2 MB) on decomposition of diazinon and its oxidized product, diazoxon, was investigated. Furthermore, these removal by the EW with CO2 MB from broccoli‐attached diazinon was examined. Diazinon was oxidized to diazoxon by EW, and the oxidative effect increased with increasing EW concentration from 0.1 to 0.6 mol L −1 or electrolyzing time from 1 to 10 min. However, EW concentration more than 0.2 mol L −1 was required to reduce diazoxon. The effect of EW on the decomposition of diazoxon increased with increasing EW concentration, electrolyzing time or reaction time from 10 to 60 min but decreased by generating CO2 MB. Furthermore, diazinon concentration in broccoli was significantly decreased by treatment with deionized water or EW for 10 min, and the removal effect was continued by generating CO2 MB in EW until 60 min. The diazoxon concentration in broccoli treated by EW decreased after increased up to 30 min, and the removal effect was increased by generating CO2 MB. Also, the pH and available chlorine concentration (ACC) of the EW increased with increasing EW concentration or electrolyzing time but decreased and almost unchanged by generating CO2 MB, respectively. Therefore, it was revealed that EW had a decomposition effect on diazinon and diazoxon and that CO2 MB promoted the effect of EW on the removal of these pesticides in broccoli. Additionally, the decomposition effect of EW on diazinon and diazoxon was suggested to be influenced by high pH and ACC. Practical Application: The EW produced from NaCl solution in a single vessel is a safer technique easy to be used than that from HCl. In addition, CO2 MB has no harmful effects on the human body. This study demonstrated that the EW was effective for decomposing diazinon, an organophosphorus insecticide, and diazoxon, its oxidized product, and that the removal of these pesticides in broccoli by the EW could be more effectively achieved by generating CO2 MB. Therefore, the use of EW with CO2 MB can be expected to remove pesticides from fruits and vegetables at food factory.